A Rhetoric of Literate Action Literate Action - Bazerman, Charles (Open textbook library., 2013)
The first in a two-volume set, A Rhetoric of Literate Action is written for "the experienced writer with a substantial repertoire of skills, [who] now would find it useful to think in more fundamental strategic terms about what they want their texts to accomplish, what form the texts might take, how to develop specific contents, and how to arrange the work of writing." The reader is offered a framework for identifying and understanding the situations writing comes out of and is directed toward; a consideration of how a text works to transform a situation and achieve the writer's motives; and advice on how to bring the text to completion and "how to manage the work and one's own emotions and energies so as to accomplish the work most effectively."